Reliability of Program Outcome Attainment Evaluation Based on Cumulative Model and Culminating Model Analysis - Anas Ibrahim; Md Rasul Mohamad Nor; Hazrina Ahmad; Muhamad Faizal Pakir Mohamed Latiff (Penerbit Universiti Kebangsaan Malaysia, 2025)
Program outcomes (POs) are essential components in outcome-based education (OBE), reflecting a graduate’s attribute and ability to demonstrate competencies at appropriate levels. Typically, POs are derived from the graduate attributes (GA) specifi ed by accrediting bodies such as the Engineering Accreditation Council (EAC). The attainment of POs is assessed through various methods, including direct and indirect assessment tools. This study evaluates the reliability and effectiveness of POs attainment analysis and measurement using cumulative model and culminating model approaches. The analysis was conducted on a cohort of 226 students who graduated in September 2017, consisting of two entry channels: 115 diploma students and 111 matriculation students. Comparative analysis results indicate that both models reliably measure POs attainment, however the culminating model shows better performance of POs attainment compared to the cumulative model. The average percentage difference between the two models for diploma students is 4.64% and no difference for PO9 and PO10. For the matriculation intake group the average percentage difference between the two models is 3.82% and no difference for PO6 and PO11. In conclusion, both models facilitate systematic POs attainment analysis for all students and provide insights into the strengths and limitations of each model, contributing to the ongoing improvement of OBE practices and ensuring that graduates meet the required competencies and standards.